Avaliação da técnica radiográfica para otimização da aquisição de imagens mamográficas - Venâncio, Rianne Brito (2017)
Mammography is the most effective method for the early detection of breast cancer. Current mammography systems are manufactured to automatically choose the technique that will be used in mammography, based only on breast thickness and not on anatomy and composition (AEC). The breast tissue has structures that have very similar attenuation coefficients, an optimized technique is required to result in an image with quality and lowest possible dose for the patient. The objective of this work is to evaluate the image quality in a FFDM mammography system considering the variation of the parameters of the image acquisition techniques. So, highlight the best combination of parameters that favors contrast, low noise and lower dose. The work was divided in three steps: The first one consisted of evaluating the mammography image from PMMA (polymethylmethacrylate) images, where the gray level variation was verified at different points of the irradiated field. The second step, in turn, evaluated the noise in images of PMMA plates following the tests proposed by the European protocol. Finally, the third step consisted in evaluating the noise and the dose in an anthropomorphic phantom. At this step the tests were performed using the rhodium filter (Rh) and the silver filter (Ag), in order to relate them to the dose and the quality of the mammography image. The results obtained in the first step prove that the correction of the Heel effect made by the FFDM mammography systems, and t it eliminates any significant influence on the image contrast of along full field; in the second step, the CNR obtained the best values at the lowest voltages tested (24, 26 and 30 kVp) for PMMA thicknesses with three, five and seven centimeters, respectively; The SNR is within the recommended values. The FOM presented the best results for the largest CNRs. In the third step the W / Rh combination showed higher CNR, in the images acquired with the W / Ag combination the CNR variation was much lower for the tested voltages. The SNR values did not show significant variation between the tensions tested for the two combinations W/Rh and W/Ag; The FOM showed the best performance for the images acquired with the W/Ag combination, and the best acquisition technique with 32 kVp. This practical work made it possible to analyze the behavior of acquisition techniques in situations that resemble the real breast situation.